Strain identification and 5S rRNA gene characterization of the hyperthermophilic archaebacterium Sulfolobus acidocaldarius. - Durovic, P (1994)
A commonly used laboratory Sulfolobus strain has been unambiguously identified as Sulfolobus acidocaldarius DSM639. The 5S rRNA gene from this strain was cloned and sequenced. It differs at 17 of 124 positions from the identical 5S rRNA sequences from Sulfolobus solfataricus and a strain apparently misidentified as S. acidocaldarius. Analysis of the transcripts from the 5S rRNA gene failed to identify any precursor extending a significant distance beyond the 5' or 3' boundary of the 5S rRNA-coding sequence. This result suggests that the primary transcript of the 5S rRNA gene corresponds in length (within 1 or 2 nucleotides) to the mature 5S rRNA sequence found in 50S ribosomal subunits.